2020
DOI: 10.1039/d0ra07224a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rice and wheat flour by particle nebulization ICP-MS

Abstract: A simple and green particle nebulization ICP-MS method for the direct measurement of trace toxic elements in rice and wheat samples was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…One of the experimental works performed using particle nebulization ICP-MS method showed interesting findings. Although it was principally different from transportation efficiency by laser ablation, it was found that very fine particles (~1 µm) can be achieved to ensure efficient particle transportation, ionization, and recoveries comparable with those of the standard solutions containing equivalent concentrations of the analyte [ 28 ]. This emphasizes that sufficient small particles are obtained with and uniform sizes during the process.…”
Section: Resultsmentioning
confidence: 99%
“…One of the experimental works performed using particle nebulization ICP-MS method showed interesting findings. Although it was principally different from transportation efficiency by laser ablation, it was found that very fine particles (~1 µm) can be achieved to ensure efficient particle transportation, ionization, and recoveries comparable with those of the standard solutions containing equivalent concentrations of the analyte [ 28 ]. This emphasizes that sufficient small particles are obtained with and uniform sizes during the process.…”
Section: Resultsmentioning
confidence: 99%
“…8.2.5 Cereals. Shi et al 59 investigated direct nebulisation of solid particles for the determination of the As, Cd, Hg and Pb content in wheat and rice by ICP-MS. These two grains form the basis of the majority of diets across the globe, so ensuring that the levels of these toxic elements are very low is important.…”
Section: Applications: Foods and Beveragesmentioning
confidence: 99%
“…This approach offers a high throughput alternative to traditional digestion methods. The first procedure, 59 applied to the determination of heavy metals in rice and wheat flour, required particle sizes smaller than 3.3 to 3.5 μm to achieve efficient transportation and ionisation and to allow calibration against aqueous standards. The results of the analysis of SRMs ranged from 94% to 107% of the certified values and RSDs were between 0.4% and 6.5%.…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%